Application of diversified follow-up in diet management of patients with maintenance hemodialysis (多元化随访方式在维持性血液透析患者饮食管理中的应用) - LI Caimei (李彩梅); SHI Chunlian (施春连); REN Yunfeng (任云凤); WANG Jinqiong (王进琼) (中西医结合护理)
Objective To evaluate the application of diversified follow-up in diet management of patients with maintenance hemodialysis. Methods Totally 68 patients undergoing maintenance hemodialysis were randomly divided into the observation group and control group, with 34 cases in each group. Patients in the control group received routing follow-up method in diet management during hemodialysis, and patients in the observation group were given diversified follow-up in the diet management, and follow-up by using telephone, email, on line consultation and face-to-face conversation were carried out according to patient needs and preference. The awareness of diet management, nutrition status during follow-up, patient compliance with prevention of diet-associated complication and incidence of diet-associated complication were observed and compared between two groups. Results The score of assessment on diet management awareness increased in both two groups after intervention, and score of observation group was higher than that in the control group(P＜0. 01). After one year follow-up, the proportion of patients with malnutrition in the observation group was lower than that in the control group(P＜0. 05). The score of compliance assessment increased in both two groups as duration of follow-up extended, and score of observation group was higher than that in the control group(P＜0. 05), and incidence of diet-associated complication in the observation group was lower than that in the control group(P＜0. 05). Conclusion The diversified follow-up helps to increase patients’ awareness of diet knowledge and improve the nutritional status and quality of life during the hemodialysis. (目的 探讨多元化随访方式在维持性血液透析患者饮食管理中的应用效果。方法 选择2022年1月—2023年1月医院收治的68例行维持性血液透析治疗的患者为研究对象, 采用随机数字表法分为观察组和对照组, 各34例。对照组给予常规电话随访; 观察组在对照组基础上实施多元化随访管理, 根据患者的需求和偏好选择包括电话随访、微信随访、家庭随访和面对面随访方式。评估患者对血液透析饮食管理的认知水平, 调查患者随访期间营养状况, 以及患者预防饮食相关并发症的依从性及并发症的发生率。结果 干预后, 两组患者对饮食管理认知评分高于干预前(P＜0. 05), 且观察组评分高于对照组, 差异有统计学意义(P＜0. 01)。随访1年, 观察组营养不良患者比例低于对照组, 差异有统计学意义(P＜0. 05)。随访开始后, 两组预防饮食相关并发症的依从性评分均较随访前提升, 且观察组评分高于对照组, 差异有统计学意义(P＜0. 05); 且观察组饮食相关并发症发生率低于对照组, 差异有统计学意义(P＜0. 05)。结论 多元化随访方式能够提高维持性血液透析患者对饮食管理知识的掌握程度, 改善患者的营养状况, 提高生活质量。)